Projection Algorithms for Variational Inclusions - Youli Yu; Pei-Xia Yang; Khalida Inayat Noor (Journal of Applied Mathematics)
We present a projection algorithm for finding a solution of a variational inclusion problem in a real Hilbert space. Furthermore, we prove that the proposed iterative algorithm converges strongly to a solution of the variational inclusion problem which also solves some variational inequality.